Implementasi Peraturan Daerah Nomor 3 Tahun 2019 Dalam Rangka Pelayanan Pengaduan di Dinas Pemberdayaan Perempuan dan Perlindungan Anak Provinsi Sumatera Utara - Afanin Syifa Aprilia; Agung Saputra (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
The Office of Women's Empowerment and Child Protection of North Sumatra Province, this organization is named the Bureau of Women's Empowerment, Children and Family Planning, North Sumatra Province Regional Secretariat which was formed in accordance with Regional Regulation number 7 of 2008 concerning Regional Secretariats and North Sumatra Provincial DPRD Secretariats. The vision of the Office of Women's Empowerment and Child Protection in North Sumatra Province is the realization of gender equality, protection of women and children and improvement of family welfare for officials and the public. This study aims to find out how to implement regional regulation number 3 of 2019 in the complaint service at the women's empowerment and child protection service. The research method used in this study is a qualitative research method with a descriptive approach with primary and secondary data types obtained through interviews with sources, and through literature and documentation studies. The results of this study indicate that in general the process of implementing complaint services at the women's empowerment and child protection service runs according to existing procedures, even though in the Covid-19 condition, people can make reports online using the official website of the women's empowerment and child protection service. Even though people report online, reports that come into the office will be processed as soon as possible. This year, the public can report directly to the UPTD. P2TP2A. the planning that will be carried out by the women's empowerment and child protection service will make an online-based complaint through an application.